Progesterone Receptor Expression in Histopathological Subtypes of Beningn Orbitocranial Meningiomas - Naima Lassie; Agus Supartoto (Majalah Oftalmologi Indonesia, 2016)
Background: Meningioma is the most common benign brain tumor which has several subtypes histopathologically.Previous studies indicate that progesterone receptors (PR) plays important role in thetumor behavior and may determine its prognosis. However, whether different subtypes show similarPR expression remains unclear. This study aimed to evaluate PR expression, in many histopathologicalsubtypes of benign orbitocranial meningiomas.Methods: Eighty one patients visiting Sardjito General Hospital with benign orbitorcranial meningioma(WHO grade I) between 2010-2013 were included. Tumor specimens were obtained for histopathologyassessment and PR expression using immunohistochemistry examination, including the intensity ofexpression.Results: There were 72 (88.9%) women and 9 (22.2%) men, aged between 21-72 years old. PR waspositive in 71.6% patients (76.4% women). There were different subtypes of meningioma as follows:meningotheliomatous (44.4%), transitional (33.3%), and fibrous (14.8%). PR was positive in 72.2%meningotheliomatous, 70.4% in transitional, and 66.7% fibrous subtype. Other subtypes of benignmeningioma (microcystic, angiomatous, lymphoplamocyte-rich, and metaplastic) were not found inour study. But, this finding was not statistically significant using Pearson correlation test (p>0.05).Conclusion: The majority of patients with meningioma were women. The most common histopathologicalsubtypes were meningotheliomatous and transitional, of which more than 70% was PR positive.However, there were very little variations in PR expression among different subtypes of benign orbitocranialmeningioma.Â Keywords: orbitocranial meningioma, progesterone receptor (PR) expression, histopathological subtype